Proceedings of the 2019 CHI Conference on Human Factors in Computing Systems 2019
DOI: 10.1145/3290605.3300361
|View full text |Cite
|
Sign up to set email alerts
|

Self-Control in Cyberspace

Abstract: Many people struggle to control their use of digital devices. However, our understanding of the design mechanisms that support user self-control remains limited. In this paper, we make two contributions to HCI research in this space: first, we analyse 367 apps and browser extensions from the Google Play, Chrome Web, and Apple App stores to identify common core design features and intervention strategies afforded by current tools for digital self-control. Second, we adapt and apply an integrative dual systems m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(23 citation statements)
references
References 154 publications
(217 reference statements)
0
21
0
Order By: Relevance
“…For example, upon switching windows, users may be presented with a message regarding their switching behaviour, prompting them to reflect on whether it is necessary to switch immediately, or whether they should postpone this switch to collect the required information later. Showing a message at the moment of switching windows fits with the model proposed by Lyngs et al [26], which uses the underlying cognitive mechanisms of self-regulation to frame self-regulation difficulties in ICT use. From the perspective of the model, difficulties occur because at the time of action, people's usage goals are either not strongly represented in working memory, or the value of meeting these goals is too low to control behaviour.…”
Section: Design Implicationsmentioning
confidence: 67%
See 1 more Smart Citation
“…For example, upon switching windows, users may be presented with a message regarding their switching behaviour, prompting them to reflect on whether it is necessary to switch immediately, or whether they should postpone this switch to collect the required information later. Showing a message at the moment of switching windows fits with the model proposed by Lyngs et al [26], which uses the underlying cognitive mechanisms of self-regulation to frame self-regulation difficulties in ICT use. From the perspective of the model, difficulties occur because at the time of action, people's usage goals are either not strongly represented in working memory, or the value of meeting these goals is too low to control behaviour.…”
Section: Design Implicationsmentioning
confidence: 67%
“…Several participants disliked the feeling that the software was controlling them, and rather wanted to learn how to gain control themselves over their work and interruptions. In line with this finding, Lyngs et al [26] argue for supporting people to develop their own regulation strategies. They evaluated 367 apps and browser extensions that aim to support digital self-control, and found that blocking distractions or removing features were the most common approaches.…”
Section: Interventions To Improve Focusmentioning
confidence: 85%
“…With rising concerns over problematic technology use, HCI research in recent years has begun promoting, or designing for, 'digital wellbeing' or enhanced 'self-control' [21,69,74]. In this space, technology use interventions have been: designed or experimented with in HCI [26, 60-62, 65, 71, 100]; deployed within operating systems (e.g.…”
Section: Favouring In Social Media Designmentioning
confidence: 99%
“…app usage limits) and utilise action schema competition to control user behaviour (e.g. app removal) [69]. These app usage and blockers can be used for all types of services -not just social media.…”
Section: Favouring In Social Media Designmentioning
confidence: 99%
“…usage tracking and data visualisations) and interventions (e.g. phone and app timers or blockers) [48]; Lyngs et al similarly categorise 'digital self-control tools' into themes of self-tracking, service blocking or removal, goal-setting, and reward or punishment mechanisms [45].…”
Section: Introductionmentioning
confidence: 99%